Study on species diversity of deciduous broad-leaved forest at Tiantai Mountain of Zhejiang Province - JIN Ze-xin (浙江大学学报. 农业与生命科学版)
The species diversity of the deciduous broad-leaved forest at the Tiantai Mountain of Zhejiang Province is studied by using such indexes as species richness, species diversity and community evenness. and comes to the following conclusion. The species richness and diversity of the woody plants are obviously bigger than those of herbs, and both of their community evennesses have no great difference. The relationship between plant biotype and species diversity shows that the species richness of tree layer is obviously smaller than that of shrub layer and that there is no big difference between their species diversity indexes, and that the community evenness of tree layer is much bigger than that of shrub layer. The species richness and diversity indexes of tree layer and shrub layer are much bigger than those of herb layer. There is no remarkable difference among the community evennesses of tree, shrub and herb layers. In terms of the community species abundance disstribution. both woody plants and herbs conform to the logarithmic series distribution, which indicates that the community has less dense species and more sparse species, and that the community evenness is relatively smaller.